THE IMPACT OF STORMWATER ON A SOIL PROFILE IN AN INFILTRATION BASIN - Winiarski T.; Bedell J.-.; Delolme C.; Perrodin Y. (My University, 2006)
The effects of urban stormwater on the soil of an infiltration/ holding basin were studied within the framework of research carried out by OTHU (Urban Hydrology Field Observatory of Lyon, France). The biophysicochemical impacts of stormwater from an industrial watershed on the local soil (to a depth of 4 m in the unsaturated zone) were measured. Several types of measurement (pH, organic matter, particle size, heavy metals content, and heterotrophic viable bacterial counts) for three vertical soil profiles were carried out. High concentrations of heavy metals and significant variations in pH and silt to a depth of 1.5 m were observed. The concentrations decreased as a function of distance from the stormwater discharge pipe. Changes in the bacterial population were also observed, varying in accordance with the depth and location of the profile.
Keywords: CONTAMINATION; BIOLOGIC CONDITIONS; STORMWATER; URBAN GROUNDWATER INFILTRATION; UNSATURATED ZONE